2020
DOI: 10.3855/jidc.10924
|View full text |Cite
|
Sign up to set email alerts
|

β-lactam and fluoroquinolone resistance in Enterobacteriaceae from imported and locally-produced chicken in Mozambique

Abstract: Introduction: Plasmid-mediated resistance to β-lactam and fluoroquinolone antibiotics was investigated in Enterobacteriaceae isolated from retailed frozen chickens from Brazil, South Africa and Mozambique. Methodology: Carcass swabs and the liquid thaw of 33 chickens from each of the three countries constituted the total sample size of 198. Isolates were identified by biochemical tests, antibiotic susceptibility was ascertained by the disc diffusion assay and β-lactamases were detected using the double-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
3
3
0
Order By: Relevance
“…The bla SHV variants (23.7%), CTX-M Group 9 variants (15.8%), and ba TEM -variants (15.8%) were the most predominant ESBL genes. Similar results were obtained by Faife et al [47], who reported bla SHV (85.0%), followed by the Bla CTX-M group (62.9%) and bla TEM (44.4%), among the E. coli isolated from imported and locally produced chicken in Mozambique. However, according to Faife et al [47], it is difficult to understand the contribution of local isolates to resistance genes, since some of the chickens were imported.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The bla SHV variants (23.7%), CTX-M Group 9 variants (15.8%), and ba TEM -variants (15.8%) were the most predominant ESBL genes. Similar results were obtained by Faife et al [47], who reported bla SHV (85.0%), followed by the Bla CTX-M group (62.9%) and bla TEM (44.4%), among the E. coli isolated from imported and locally produced chicken in Mozambique. However, according to Faife et al [47], it is difficult to understand the contribution of local isolates to resistance genes, since some of the chickens were imported.…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were obtained by Faife et al [47], who reported bla SHV (85.0%), followed by the Bla CTX-M group (62.9%) and bla TEM (44.4%), among the E. coli isolated from imported and locally produced chicken in Mozambique. However, according to Faife et al [47], it is difficult to understand the contribution of local isolates to resistance genes, since some of the chickens were imported. Among E. coli isolates from children with enteric diarrhea, at the Maputo Central Hospital, Mozambique, Berendes et al [15] found 68% of the isolates with the bla SHV variants and 20% with the prevalence of the CTX-M Group 9.…”
Section: Discussionsupporting
confidence: 89%
“…Because the poultry environment is continually in contact with humans, a high prevalence of resistant bacterium genes in the environment may raise the danger of transfer to humans. In current study out of 6 isolates, all isolates were positive for (bla-tem, blaCTX-M and bla-SHV) genes, this result is in agreement with the study by Faife et al,(2020), While this study is not in agreement to the study by Akinbami et al (2018)., It was discovered that 10.4 percent of C. freundii isolates tested positive for the bla-tem gene. Bla-tem gene was the most prevalent ESBL gene detected followed by bla-SHV and blaCTX-M genes in clinical isolates (Sedighi et al, 2017 andOlajumoke et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…Enteric bacterial isolates, detected in food-producing animals and meat and in particular in poultry and chicken meat isolates are commonly resistant to antibiotics critically important to human medicine like third-generation cephalosporins and quinolones in addition to ampicillin, tetracyclines and co-trimoxazole [118]. This is true in LMICs as well with poultry and pork farming the major role players as generators of ABR across a range of bacterial culprits [119][120][121][122]. An alarming concern, is the acquired colistin resistance in food-borne pathogens seen across several countries in animals and humans (i.e., associated with infection) [123].…”
Section: Antibiotic Uses In Animal Health and The Agricultural Sectormentioning
confidence: 99%